Dinamika Kontrol Diri pada Ibu Bekerja yang Menjalani Latihan Yoga - Kadek Anindita Widyasari; I Gusti Ayu Diah Fridari (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2013)
Nowadays, the number of mother worked increasingly increased either as a part-time or full time worker. In Encyclopedia of Children’s Health, working mother is a situation where a mother working outside the home to earn income in addition to taking care of children at home. The classification of working mother is a woman who has children ranging in age from 0-18 years and a workforce (Lerner, 2001). On 2001, number of working mothers in the world reached 54,3% (OECD, 2001), which is the dual role required along with current technological advances. Beside economic factors, the mother’s participation in employment is also influenced by social, political and demographic (Bower, on Reynolds et. al, 2003). In this case, self-control is important because the decision of a mother to act in the face of variety of circumstances few would least affect the atmosphere of the household itself. Awareness of the importance of self-control will make the mother trying to raise her self-control, one of which is doing Yoga exercises. This study use qualitative method and phenomenological approach, with 3 of working mother. The result show that there is an increase in the quality of self-control on working moms who do Yoga exercises seen from the aspect of behavioral control, cognitive control, decisional control and the process of Yoga asana, pranayama and meditation in the Yoga session Keywords: self-control, working mother, yoga